Extinction and the Anatidae of New Zealand - Williams, G R (Wildfowl, 1964)
The historical and present status of each species of Anatidae found in New Zealand is described and causes of change are discussed. Of 19 native or self-introduced species believed to have bred, five natives and two Australian stragglers became extinct before European settlement. Mergus australis is the only native species to have become extinct since 1800. Seven native species survive: all but two have been reduced in numbers or range, or both. The Grey Teal and the Shoveler continue to thrive. The two in greatest danger are the Brown Teal and the Blue Duck. Destruction of habitat is the most serious threat. Four species have been successfully established and four others have been stragglers from Australia in European times.